Diversity of rumen microbiota using metagenome sequencing and methane yield in Indian sheep fed on straw and concentrate diet - Malik, P.K.; Trivedi, S.; Kolte, A.P.; Sejian, V.; Bhatta, R.; Rahman, Habibur (Elsevier, 2022)
An in vivo study aiming to investigate the rumen methanogens community structure was conducted in Mandya sheep fed on straw and concentrate diet. The ruminal fluid samples were collected and processed for unravelling the rumen microbiota and methanogens diversity. Further, the daily enteric methane emission and methane yield was also quantified using the SF6 tracer technique. Results indicated that the Bacteroidetes (∼57%) and Firmicutes (25%) were two prominent affiliates of the bacterial community. Archaea represented about 2.5% of the ruminal microbiota. Methanobacteriales affiliated methanogens were the most prevalent in sheep rumen. The study inveterate that the ruminal archaea community in sheep is composed of 9 genera and 18 species. Methanobrevibacter represented the largest genus of the archaeome, while methylotrophs genera constituted only 13% of the community. Methanobrevibacter gottschalkii was the prominent methanogen, and Methaobrevibacter ruminantium distributed at a lower frequency (∼2.5%). Among Methanomassiliicoccales, Group 12 sp. ISO4-H5 constituted the most considerable fraction (∼11%). KEGG reference pathway for methane metabolism indicated the formation of methane through hydrogenotrophic and methylotrophic pathways, whereas the acetoclastic pathway was not functional in sheep. The enteric methane emission and methane yield was 19.7 g/d and 20.8 g/kg DMI, respectively. Various species of Methanobrevibacter were differently correlated, and the distribution of hydrogenotrophic methanogens mainly explained the variability in methane yield between the individual sheep. It can be inferred from the study that the hydrogenotrophic methanogens dominate the rumen archaeal community in sheep and methylotrophic/aceticlastic methanogens represent a minor fraction of the community. Further studies are warranted for establishing the metabolic association between the prevalent hydrogenotrophs and methylotrophs to identify the key reaction for reducing methane emission.